2006
DOI: 10.1038/ja.2006.59
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Quinolactacin A, a TNF Production Inhibitor

Abstract: Quinolactacins, which inhibit tumor necrosis factor production, contain a quinolone skeleton conjugated with a g -lactam. The biosynthesis of quinolactacin was investigated by feeding experiments using 13 Keywords quinolactacin, quinolone, biosynthesis, 13 C labeled precursor, Penicillium sp. IntroductionSince entomopathogenic fungi possess a parasitic function, it was expected that novel biologically active compounds such as insecticides and immunosuppressants would be isolated from them [1ϳ7]. In the course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
(44 reference statements)
3
15
0
Order By: Relevance
“…The chiral phase of HPLC analysis showed that were two conjoint peaks that could not separate well, also 2 dissolved in a solvent that was unstable and then changed to quinolactacin D, as speculated in the reference [10]. Compound 2 appeared to be synthesized from kynurenine and leucine, which was similar to the speculation reported by Nakagawa et al [11]; shown in Figure S1. Thereby, 2 was elucidated as a pair of enantiomers and named quinolactacin E.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The chiral phase of HPLC analysis showed that were two conjoint peaks that could not separate well, also 2 dissolved in a solvent that was unstable and then changed to quinolactacin D, as speculated in the reference [10]. Compound 2 appeared to be synthesized from kynurenine and leucine, which was similar to the speculation reported by Nakagawa et al [11]; shown in Figure S1. Thereby, 2 was elucidated as a pair of enantiomers and named quinolactacin E.…”
Section: Resultssupporting
confidence: 74%
“…SCSIO41015. The new structures were elucidated by analysis of their NMR data and HR-ESI-MS. Their absolute configurations were established by single-crystal X-ray diffraction analysis or a comparison of the experimental with the reported specific rotation values.The biosynthetic pathway of quinolactacin A has been studied, andspeculated that it is synthesized from tryptophan and isoleucine [11]. Based on the current investigation, possible biosynthetic pathways of alkaloids 1 , 2 , and 4 – 6 were speculated.Compound 2 appeared to be synthesized from tryptophan and leucine, whereas compound 4 was made from tryptophan and valine.…”
Section: Discussionmentioning
confidence: 99%
“…S11, ESI †). 8 Some biosynthetic studies have been reported for the fungal phenalenones such as deoxyherqueinone 9 and atrovenetin 10 (Fig. Thus, compounds 3, 6, 8, 12 and 15 showed significant inhibition of the protease human leukocyte elastase (HLE) with IC 50 values of 7.2, 10.9, 13.3, 9.3 and 3.0 μM, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…EPF-6. 26 With this result to hand, we searched the publicly available F. equiseti genome for a potential biosynthetic gene cluster (BGC) encoding homologues of known tryptophan dioxygenase (TDO) and dimethylallyl diphosphate ( prenyl) transferase (DMAT) enzymes. This immediately revealed a gene cluster (Scheme 2b, Tables 1 and S1 †) encoding 10 predicted proteins Organic & Biomolecular Chemistry Paper of significance.…”
Section: Papermentioning
confidence: 99%